Pharmacological Evaluation of Naproxen Metal Complexes on Antinociceptive, Anxiolytic, CNS Depressant, and Hypoglycemic Properties - Md. Sharif Hasan; Narhari Das; Zobaer Al Mahmud; S. M. Abdur Rahman (Hindawi Limited, 2016)
Purpose. The present study was designed to investigate the antinociceptive, anxiolytic, CNS depressant, and hypoglycemic effects of the naproxen metal complexes. Methods. The antinociceptive activity was evaluated by acetic acid-induced writhing method and radiant heat tail-flick method while anxiolytic activity was evaluated by elevated plus maze model. The CNS depressant activity of naproxen metal complexes was assessed using phenobarbitone-induced sleeping time test and the hypoglycemic test was performed using oral glucose tolerance test. Results. Metal complexes significantly (P<0.001) reduced the number of abdominal muscle contractions induced by 0.7% acetic acid solution in a dose dependent manner. At the dose of 25 mg/kg body weight p.o. copper, cobalt, and zinc complexes exhibited higher antinociceptive activity having 59.15%, 60.56%, and 57.75% of writhing inhibition, respectively, than the parent ligand naproxen (54.93%). In tail-flick test, at both doses of 25 and 50 mg/kg, the copper, cobalt, silver, and zinc complexes showed higher antinociceptive activity after 90 minutes than the parent drug naproxen. In elevated plus maze (EPM) model the cobalt and zinc complexes of naproxen showed significant anxiolytic effects in dose dependent manner, while the copper, cobalt, and zinc complexes showed significant CNS depressant and hypoglycemic activity. Conclusion. The present study demonstrated that copper, cobalt, and zinc complexes possess higher antinociceptive, anxiolytic, CNS depressant, and hypoglycemic properties than the parent ligand.